The Hygia Project and Hygia Chronotherapy Trial: insights of we clinical investigators on the impact of the embedded continuing medical education on primary-care practice and improved patient cardiovascular health. (3rd May 2020) - Crespo, Juan J.; Domínguez-Sardiña, Manuel; Otero, Alfonso; Moyá, Ana; Ríos, María T.; Sineiro, Elvira; Castiñeira, María C.; Callejas, Pedro A.; Pousa, Lorenzo; Salgado, José L.; Durán, Carmen; Sánchez, Juan J.
ABSTRACT: The participating doctors of the Hygia Chronotherapy Trial (HCT) are aware of the criticisms of its published findings, which have been unjustifiably misrepresented in letters to the editors and commentaries, perhaps because of lack of understanding of the foundations of the Hygia Project, in which the HCT is nested. Thus, our purpose through this communication is to highlight the unique features of the Hygia Project and HCT in terms of: (i) organization, management, and quality control, (ii) physician training/continuing medical education, and (iii) impact on every-day primary-care clinical practice specifically improved patient care through 48 h ambulatory blood pressure monitoring to diagnose and optimally manage by bedtime hypertension chronotherapy true arterial hypertension to markedly improve the cardiovascular health of our patients.